1998
DOI: 10.1111/j.1440-1819.1998.tb01009.x
|View full text |Cite
|
Sign up to set email alerts
|

An attempt of radar chart expression of a self‐rating scale for sleep disturbance

Abstract: We made an attempt to express a complaint of sleep disturbance by a self‐rating scale of radar chart mode. The questionnaire for sleep disturbance is made up of eight items. Each item was scored from grade 1 to 4. The score of each item was projected to the MY radar chart, designed by us. It is noted that this method is useful in following the effect of hypnotics on sleep disturbance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The present study showed that lunchtime bright light exposure administered for 3 weeks to patients with and without dementia in a geriatric hospital ameliorated their nocturnal sleep and daytime wakefulness. Previous reports suggested that bright light therapy was effective in patients with dementia 3–5 . The findings of the present study suggest that lunchtime bright light therapy may improve sleep–wakefulness patterns.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The present study showed that lunchtime bright light exposure administered for 3 weeks to patients with and without dementia in a geriatric hospital ameliorated their nocturnal sleep and daytime wakefulness. Previous reports suggested that bright light therapy was effective in patients with dementia 3–5 . The findings of the present study suggest that lunchtime bright light therapy may improve sleep–wakefulness patterns.…”
Section: Discussionsupporting
confidence: 66%
“…Nurses performed daily ratings each shift (day and night) for sleep–wakefulness disturbances according to the modified MY (Matsubara Yamaguch) radar chart 5 . The rating scale is made up of eight items.…”
Section: Methodsmentioning
confidence: 99%
“…As with other forms of radial plotting, the use of radar charts in the medical literature is rare, but present. Yamaguchi et al [19] used radar charts for monitoring multiple-item self-ratings of sleep disturbance over time; Kosaka et al [20] used radar charts to express quality-of-life factors in breast surgery patients; Minemawari and Kato [21] used the radar chart as a geriatric assessment system; and Jette and Jette [22] present comparisons of health-outcome data measured using various questionnaires with radar charts.…”
Section: Radar Plots In Medical Researchmentioning
confidence: 99%
“…A particular radial plotting technique, called the ''radar plot,'' has been frequently used for graphing multivariate data in the health care field [14,18]. It is easy to implement with the most common software; however, the interpretation of the results strongly depends on the ordering of the indicators being displayed, and the presence of missing information for some indicators is impossible to distinguish from the ''zero'' value for other indicators.…”
Section: Introductionmentioning
confidence: 99%